2016
DOI: 10.1186/s41038-016-0032-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the wound healing potential of isoquercetin-based cream on scald burn injury in rats

Abstract: BackgroundThe present study was designed to evaluate the potential of isoquercetin-based cream formulation on scald burn wound injury in rats.MethodsFour isoquercetin-based cream formulations viz. 0.01, 0.02, 0.04, and 0.06 % w/w were prepared. Cream base and standard anti-burn cream containing silver sulfadiazine were also used for comparison. Scald burn was given to rats by pouring water at 90 °C on a shaved dorsal area of 20 mm2. Deep second-degree burn injury was produced which was evaluated for the next 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
15
0
2
Order By: Relevance
“…Scalds have some slightly distinct pathophysiological characters among all types of burns, such as a more wound exudate and necrotic debris on the surface . Scald injury tends to be the most common devastating trauma that results in either disability or death of burn patient, especially childhood . The injured depth is a significant determinant of mortality and the primary determinant of the patient's long‐term appearance and functional outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Scalds have some slightly distinct pathophysiological characters among all types of burns, such as a more wound exudate and necrotic debris on the surface . Scald injury tends to be the most common devastating trauma that results in either disability or death of burn patient, especially childhood . The injured depth is a significant determinant of mortality and the primary determinant of the patient's long‐term appearance and functional outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many studies have demonstrated that the hydrogen peroxide production by tissue-resident cells (i.e., synoviocytes), macrophages and neutrophils, could favor the sensitization of nociceptors via TRPA1 activation (Moilanen et al, 2015;Trevisan et al, 2016Trevisan et al, , 2014. Previous studies reported that thermal burn might increase the reactive species production, which could contribute to the tissue damage (Bhatia et al, 2016;Hoşnuter et al, 2004;Parihar et al, 2008;Silveira et al, 2016;Tanaka et al, 1999). In this sense, antioxidants are designed to reduce production and to capture reactive species that promote tissue lesion (Wasiak et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the major advances in the treatment of burn wounds, the systemic inflammatory response syndrome (SIRS), the sepsis and multiple organ damage are the main causes of disability and death in burns [Parihar A. et al, 2008]. In this respect, thermal burn wounds are a typical example [Abdulhalli A. et al, 2014, Bhatia N. et al, 2016.…”
Section: Role Of Oxidative Stress In the Pathology Of Burns And In Hementioning
confidence: 99%
“…Microcirculation is of most importance for the degree of burns. Thermal burns cause immediate and prolonged inflammatory response that generates toxins and free radicals [Parihar A. et al, 2008, Bhatia N. et al, 2014, Bhatia N. et al, 2016, Cacir B. and Yegen BC. 2004.…”
Section: Role Of Oxidative Stress In the Pathology Of Burns And In Hementioning
confidence: 99%